2017
DOI: 10.1002/hup.2594
|View full text |Cite
|
Sign up to set email alerts
|

Recreational stimulants, herbal, and spice cannabis: The core psychobiological processes that underlie their damaging effects

Abstract: Recreational stimulants such as cocaine or MDMA (3.4-methylenedioxymethamphetamine) and sedative drugs such as cannabis damage human homeostasis and well-being through similar core psychobiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…Yet in order for this practice to become usual, psychiatrists and physicians need to be educated about its adverse effects. Mental health improves after cessation of other recreational stimulants, such as amphetamines or cocaine, and similar gains have been found following Ecstasy/MDMA cessation (Parrott, 2015;Parrott, Hayley et al, 2017). Morgan, McFie, Fleetwood, and Robinson (2002) found that current and former MDMA users displayed heightened psychopathology scores, while former users were less impaired.…”
Section: Psychiatric Disturbancesmentioning
confidence: 63%
“…Yet in order for this practice to become usual, psychiatrists and physicians need to be educated about its adverse effects. Mental health improves after cessation of other recreational stimulants, such as amphetamines or cocaine, and similar gains have been found following Ecstasy/MDMA cessation (Parrott, 2015;Parrott, Hayley et al, 2017). Morgan, McFie, Fleetwood, and Robinson (2002) found that current and former MDMA users displayed heightened psychopathology scores, while former users were less impaired.…”
Section: Psychiatric Disturbancesmentioning
confidence: 63%
“…The most common mental health consequences were mood disturbances (e.g., dysphoria), anxiety, panic attacks, sleep disturbances, and memory loss. Previous studies have attributed such consequences to the use of cannabis, ecstasy, amphetamine, and cocaine [5,29,[33][34][35][36][62][63][64], which are also the drugs most frequently used by participants in the present study. A recent meta-analysis shows that ecstasy users display deficits in the serotonergic transporter in several brain areas.…”
Section: Consequencesmentioning
confidence: 90%
“…Cocaine and amphetamine use has also been associated with an increased risk of psychotic symptoms and myocardial infarction, which in turn can trigger fatal cardiac arrhythmias and stroke [ 1 , 32 ]. In addition, regular use of cannabis and the abovementioned three central stimulants is associated with mood fluctuations, depression, anxiety, sleep disturbances, and cognitive deficits [ 5 , 29 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms of cannabis withdrawal have been formalized in standardized questionnaires such as the Cannabis Withdrawal Discomfort Scale [ 47 ], and the Marijuana Craving Questionnaire [ 48 ]. The high addictiveness of cannabis does make it difficult to understand current movements to make its usage legal [ 49 ].…”
Section: Mood State Fluctuationsmentioning
confidence: 99%
“…Hence spice displays far greater addictiveness, with some users committing suicide when they cannot access their normal drug supplies [ 6 , 29 , 55 , 56 , 57 , 58 ]. The practical consequences of cannabis dependency can be severe [ 49 ]. In the USA around 300,000 individuals approach professional drug addiction services for cannabis dependency every year [ 59 ].…”
Section: Mood State Fluctuationsmentioning
confidence: 99%